2008
DOI: 10.1529/biophysj.108.139428
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Connections Between the Nucleus and the Actin and Microtubule Networks in Laminopathic Models

Abstract: Laminopathies encompass a wide array of human diseases associated to scattered mutations along LMNA, a single gene encoding A-type lamins. How such genetic alterations translate to cellular defects and generate such diverse disease phenotypes remains enigmatic. Recent work has identified nuclear envelope proteins--emerin and the linker of the nucleoskeleton and cytoskeleton (LINC) complex--which connect the nuclear lamina to the cytoskeleton. Here we quantitatively examine the composition of the nuclear envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
194
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(229 citation statements)
references
References 61 publications
32
194
3
Order By: Relevance
“…We have recently shown that LINC complex proteins are displaced from the nucleus to the ER and cytoplasm in a majority of Lmna L530P/L530P cells (17). Similarly to Lmna Ϫ/Ϫ cells, Lmna L530P/L530P cells show no overt disorganization of their basal stress fibers compared to control WT cells (17).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We have recently shown that LINC complex proteins are displaced from the nucleus to the ER and cytoplasm in a majority of Lmna L530P/L530P cells (17). Similarly to Lmna Ϫ/Ϫ cells, Lmna L530P/L530P cells show no overt disorganization of their basal stress fibers compared to control WT cells (17).…”
Section: Resultsmentioning
confidence: 94%
“…Because the NE distribution of LINC complex proteins is altered in embryonic fibroblasts derived from mice lacking A-type lamins, a model of dilated cardiomyopathy and muscular dystrophy (15,16), we hypothesized that the depletion of lamin A/C from the nucleus would disrupt the organization of the actin cap and the regulation of nuclear shape by cell shape. While the organization of actin fibers away from the nucleus in Lmna Ϫ/Ϫ cells (imaged by focusing on the bottom of the cell) remained largely unchanged indeed (17,18), the actin cap disappeared in a majority of Lmna Ϫ/Ϫ cells (Fig. 4 A and C, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, mounting evidence indicates that www.cell-research.com | Cell Research Wenjia Wang et al 1441 npg LINC complexes function in multiple biological processes, including nuclear migration and repositioning, meiotic telomere tethering and chromatin organization, centrosome migration and attachment, nucleokinesis and cellular rigidity homeostasis [1][2][3]. Recently, LINC complexes have been implicated in the regulation of apoptosis [4,5], the maturation and survival of germlines [6], and in the pathology of human diseases linked to mutations of A-type lamins, such as laminopathies and Emery-Dreifuss muscular dystrophy [7][8][9]. During a study of centrosome-related proteins that were affected by erbB transformation, we cloned and identified the SUN domain protein SUN2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, perturbations of the intermediate filament network could alter the positioning of the nucleus in both migrating and immobile astrocytes, suggesting that cytoplasmic intermediate filaments are involved in actin-dependent positioning of the nucleus 20 . Concomitant with these recent discoveries, significant advances have been made in terms of identifying the molecular links between the nuclear envelope and the cytoplasmic filaments [21][22][23][24][25] , and new insights have been gained into the mechanistic maintenance of the nucleus 3,23,24,26,27 . Emerging evidence is now accumulating that cytoplasmic filaments are exploited by cells to govern nuclear morphology and finely tune gene expression in response to cell shape changes.…”
mentioning
confidence: 99%